2013
DOI: 10.1590/s2179-83972013000300006
|View full text |Cite
|
Sign up to set email alerts
|

Resolução do segmento ST após intervenção coronária percutânea primária: características, preditores de insucesso e impacto na mortalidade

Abstract: Background: ST-segment resolution is an important predictor of infarct-related artery patency and effective microcirculatory perfusion. The aim of this study was to compare patients with and without ST-segment elevation resolution and identify variables that are associated with failure of ST-segment resolution. Methods: Between March 2012 and July 2013, 61 patients with ST-segment elevation acute myocardial infarction underwent primary percutaneous coronary intervention (PCI) and were included in a prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…12 In an electrocardiographic subanalysis of the PLATelet Inhibition and Patient Outcomes (PLATO) trial, 70% of patients randomized in the range 3 to 6 hours of symptom onset exhibited ST-segment resolution, compared to 51% of those randomized after 6 hours. 13 A similar result was found by Andrade et al, 14 who demonstrated the association of longer ischemic time with incomplete resolution of ST-segment elevation. The survival benefits and other relevant outcomes, associated with a lower symptom onset-to-balloon time, can be observed even in long-term evolution.…”
Section: Discussionsupporting
confidence: 75%
“…12 In an electrocardiographic subanalysis of the PLATelet Inhibition and Patient Outcomes (PLATO) trial, 70% of patients randomized in the range 3 to 6 hours of symptom onset exhibited ST-segment resolution, compared to 51% of those randomized after 6 hours. 13 A similar result was found by Andrade et al, 14 who demonstrated the association of longer ischemic time with incomplete resolution of ST-segment elevation. The survival benefits and other relevant outcomes, associated with a lower symptom onset-to-balloon time, can be observed even in long-term evolution.…”
Section: Discussionsupporting
confidence: 75%
“…In this issue, Andrade et al 13 evaluated 61 patients who underwent primary PCI between March 2012 and July 2013, comparing their clinical and angiographic characteristics in relation to the resolution of the STsegment, which occurred in one third of cases. The group of patients without ST-segment resolution showed higher heart rate, prevalence of diabetes mellitus, and chronic renal failure, and a tendency to longer ischemic time; mortality was also higher in these patients.…”
Section: See Page 227mentioning
confidence: 99%